2021
DOI: 10.22456/2316-2171.102314
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Associados À Funcionalidade Familiar De Idosos Assistidos Por Uma Unidade De Saúde Da Família De Vitória – Es

Abstract: Introdução: A interação dos membros da família entre si e com outros revela se os núcleos familiares são funcionais ou disfuncionais. Objetivo: Verificar funcionalidade familiar de idosos de uma USF e sua associação com perfil socioeconômico, arranjo familiar e condições de saúde/hábitos de vida. Métodos: Estudo observacional transversal analítico com amostra probabilística aleatória de idosos (≥ 60 anos). Coletaram-se informações do perfil socioeconômico, arranjo familiar e condições de saúde/hábitos de vida.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Sobre a capacidade resolutiva, 64,6% estavam satisfeitos com a forma pelo qual seus membros organizavam atenção, diálogo e escuta. Suzana et al (2021), averiguou que a FF em seu estudo estava alterada Maria de Fátima Vieira de Sousa Gonçalves, Francisco Gomes Gonçalves, Giseli da Silva Toqueto Gomes, Daniela Maria Janjacomo Miesse, Sabrina Ramires Sakamoto ____________________________________________________________________________ em 26% da amostra sendo 13% para moderado e 13% para o grau elevado.…”
Section: Resultsunclassified
“…Sobre a capacidade resolutiva, 64,6% estavam satisfeitos com a forma pelo qual seus membros organizavam atenção, diálogo e escuta. Suzana et al (2021), averiguou que a FF em seu estudo estava alterada Maria de Fátima Vieira de Sousa Gonçalves, Francisco Gomes Gonçalves, Giseli da Silva Toqueto Gomes, Daniela Maria Janjacomo Miesse, Sabrina Ramires Sakamoto ____________________________________________________________________________ em 26% da amostra sendo 13% para moderado e 13% para o grau elevado.…”
Section: Resultsunclassified
“…Self-perception of health was investigated through the following question: "In general, how do you evaluate your health? ", and the elderly can answer between the following options: very bad; bad (considered as negative perception of health) regular, good and very good (classified as positive/regular perception of health) (SUZANA et al, 2021). Multimorbidity was determined by the presence of two or more chronic diseases, and polypharmacy by the daily use of five or more medications (SUZANA et al, 2021).…”
Section: Uniting Knowledge Integrated Scientific Research For Global ...mentioning
confidence: 99%
“…Therefore, older adults were included and studies (5,8,9) using the Family Apgar have shown that family function is influenced by the dependence of the older adult and the difficulty of adapting to this dependence (5) ; and by the family structure and the presence or absence of a partner (8) . Another study assessed the Apgar properties in Chilean older adults and found that this instrument was reliable and effective when applied to older adults, especially in rural areas (9) .…”
Section: Introductionmentioning
confidence: 99%